Cuestiones protagónicas: Crémilo y Carión en Plutos de Aristófanes (Argos, 2025)
In the scenes which illustrate the consequences of the fulfillment of the new order. Chremylos and Karion alternate in the reception of the casual visitors. The outstanding differences between scenes dominated by the former or the latter lead us to doubt the supposed protagonism shared between master and slave. The dissimilities serve to exalt the figure of Chremylos and to test his heroic makeup. Karion himself behaves as a mere receptionist.
Keywords: Plutos; Aristophanes; protagonist; comic hero; acting